Nocardia Brain Abscess and CD4+ Lymphocytopenia in a Previously Healthy Individual - Norair Adjamian; Adeline Kikam; Kathryn Ruda Wessell; Jason Casselman; Erin Toller-Artis; Olapeju Olasokan; Robert W. Hostoffer (Case Reports in Immunology)
Nocardia brain abscesses are a known occurrence in patients with immunocompromised conditions. Nocardial infection is commonly an unfortunate sequela to other complications which these patients are being followed up and treated for. The incidence of nocardial brain abscess in an otherwise healthy patient is extremely rare. We present a case of Nocardia brain abscess in a previously healthy individual, who, upon workup for vision and gait abnormalities, was shown to have multiple brain abscesses and a decreased absolute CD4+ lymphocyte count. Adding to the rarity of our case, the finding of lymphocytopenia in our patient was unrelated to any known predisposing condition or infectious state.